Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fnmol.2019.00135
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Abnormalities in the Olfactory System of Fragile X Syndrome Models

Abstract: Fragile X Syndrome (FXS) is the most common inherited form of intellectual disability. It is produced by mutation of the Fmr1 gene that encodes for the Fragile Mental Retardation Protein (FMRP), an important RNA-binding protein that regulates the expression of multiple proteins located in neuronal synapses. Individuals with FXS exhibit abnormal sensory information processing frequently leading to hypersensitivity across sensory modalities and consequently a wide array of behavioral sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 117 publications
0
8
0
Order By: Relevance
“…To begin with, three regions that are involved in olfaction, the piriform cortex, olfactory bulb, and anterior commissure were altered in Fmr1-Δ exon 8 rats. Olfaction has not been well characterized in FXS, but it is impaired in rodent models of FXS 36 . Individuals with FXS can also be hypersensitive to auditory and visual stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…To begin with, three regions that are involved in olfaction, the piriform cortex, olfactory bulb, and anterior commissure were altered in Fmr1-Δ exon 8 rats. Olfaction has not been well characterized in FXS, but it is impaired in rodent models of FXS 36 . Individuals with FXS can also be hypersensitive to auditory and visual stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of FMRP-mediated regulation of BK channel conductance (Deng et al, 2013 ; Deng and Klyachko, 2016b ) could therefore conceivably account for impaired habituation in FMR1 KO animals, although this has not been directly tested yet. While less characterized, there is evidence for altered olfaction in FXS models as well (Bodaleo et al, 2019 ). Interestingly, studies in FMR1 KO mice (Schilit Nitenson et al, 2015 ) and a FXS drosophila model (Franco et al, 2017 ) both found that FXS animals exhibited decreased odor sensitivity, contrary to findings from other sensory domains.…”
Section: Behavioral Consequences Of Hyperexcitable Circuits In Fxsmentioning
confidence: 99%
“…Our findings of significantly lower [ 18 F]FPEB binding potential (BP ND ) in these areas provide support for the role of mGluR5 in the neurobiology of FXS. Anxiety is frequently reported in this population, which may explain the significant group differences we observed in the insula and olfactory cortex 19 , 23 . Evidence in support of these findings also comes from preclinical studies of the Fmr1 KO mouse using the Morris water maze task and the mirrored chamber test 24 26 .…”
Section: Discussionmentioning
confidence: 62%